Rádio entre fronteiras: uma análise dos programas do radialista Ilário Ermindo Kehl - alemão louco (1970-2009) - Gonsalves, Rosana Déa Marques (2015)
The research objective to investigate the role of the radio as cultural practice in the border region of Western Parana state, from the 1970s on, following the trajectory of Ilário Ermindo Kelh, radio broadcaster (popularized with the Crazy German character), killed in 2009. The initial reflection focuses on documents about their programs aired on the radio in Marechal Cândido Rondon, within in this border area (Brazil/Paraguay). The data sources used are part of the personal documents. The research present radios stations as an important of communication and as work tools conflicting in the instituition of memories within in this border area